The Formulating Growth Strategy of Aceh Port System in Indonesia: An AHP Approach - Subhan, Muhammad; Abdul Ghani, Ahmad Bashawir (Gadjah Mada International Journal of Business, 2011)
The main objective of this study is to investigate the growth strategy of Acehâs ports in order to develop a better position of those ports in the dynamic and competitive environment along the Malacca straits. Using the analytic hierarchy process (AHP) approach, this study examines priority perspectives on strategy formulation from 25 individuals representing relevant parties in the Aceh port industry such as government officials, port authorities and managements, experts, academicians and consultants, and port user associations. Six potential strategies related to resources, competencies, market share, opportunity share, cooperation, and competitiveness were examined. The findings show that the resource-based strategy and the competence-based strategy are ranked as first and second important strategy respectively while the opportunity share strategy ranked as the least important strategy. This study provides new insights into the implications of using various strategy formulations for port growth in developing countries and provides a significant practical contribution to the port authorities.Â Â Â Â Â